Immunological changes and increased expression of myxovirus resistance protein a in thyroid tissue of patients with recent onset and untreated Graves' disease - Hammerstad SS; Jahnsen FL; Tauriainen S; Hyöty H; Paulsen T; Norheim I; Dahl-Jørgensen K. (Mary Ann Liebert, Inc., 2022)
Background: Few studies have systematically examined the immune cells that infiltrate thyroid tissue at the time of the onset of Graves' disease (GD). The role of viruses in the pathogenesis of autoimmune thyroid diseases is controversial. The present study analyzed inflammatory responses with respect to signs of virus infection.
Methods: Thyroid tissue was obtained from 22 patients with newly diagnosed and untreated GD, 24 patients with chronic GD, and 24 controls. Inflammation was assessed by immunostaining for CD4+ and CD8+ T cells, plasma cells (CD138+), and plasmacytoid dendritic cells (PDCs). The production of interferon-inducible myxovirus resistance protein A (MxA) was analyzed as a sign of virus infection.
Results: The degree of thyroid inflammation and fibrosis was significantly higher in both patient groups compared with that in controls. The number of CD4+ T cells and plasma cells (activated B cells) was significantly higher in both patient groups. CD8+ cells were only present in patients with chronic disease. MxA expression and the number of PDCs increased only in patients with newly diagnosed GD. There was a strong positive correlation between the number of PDCs and the number of MxA+ leucocytes.
Conclusion: The increase in CD8+ T cells during the chronic stage of GD suggests that they may play a role in progression of the autoimmune process from early to chronic thyroiditis. Upregulation of MxA expression during the early stages of the disease, and the positive correlation between the number of PDCs and the number of MxA+ leucocytes, suggests that activated PDCs secrete type I IFNs at the lesion site, possibly in response to viral infection.